2002
DOI: 10.1034/j.1600-6143.2002.20908.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Enzyme-Linked Immunosorbent Spot Assay for Post-Transplant Alloreactivity as a Potentially Useful Immune Monitoring Tool

Abstract: Post-transplant monitoring of cellular immunity has the potential to guide alterations in medical therapy. To this end, our laboratory has developed an enzymelinked immunosorbent spot (ELISPOT) assay for detection of peripheral blood alloimmunity. Peripheral blood lymphocytes (PBLs) from normal volunteers and from renal allograft recipients were tested against donor stimulator cells for their ability to respond in 'one-way' cytokine ELISPOT assays. T cell depletion of donor spleen or PBLs eliminated donor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 24 publications
6
84
1
Order By: Relevance
“…In addition, the assay has been optimized for use of frozen cells that can be easily stored. Although no studies to date have reported the use of this assay to identify functionally tolerant humans after transplantation, the frequency of IFN-␥-producing cells has been reported to correlate with the incidence of acute and chronic rejection as well as allograft function after renal transplantation (45)(46)(47). Obtaining and storing sufficient numbers of donor cells to perform the assay repeatedly is a practical limitation, particularly in recipients of deceased-donor organs.…”
Section: Elispot Assaymentioning
confidence: 99%
“…In addition, the assay has been optimized for use of frozen cells that can be easily stored. Although no studies to date have reported the use of this assay to identify functionally tolerant humans after transplantation, the frequency of IFN-␥-producing cells has been reported to correlate with the incidence of acute and chronic rejection as well as allograft function after renal transplantation (45)(46)(47). Obtaining and storing sufficient numbers of donor cells to perform the assay repeatedly is a practical limitation, particularly in recipients of deceased-donor organs.…”
Section: Elispot Assaymentioning
confidence: 99%
“…Indeed, CTLs that make other cytokines are viewed as unusual, and IFN-␥ production has often been used to enumerate antigen-specific CTLs. 58,59 IL-12 is a key cytokine for CTL differentiation from resting CD8 ϩ T cells. 56 As discussed above, the ability of IL-12 and IL-18 to promote the antigen-driven development of T H 1 immunity is well established.…”
Section: Ccr7mentioning
confidence: 99%
“…IFN-␥ and IL-10 ELISPOT assays were performed as described previously in detail (36,37). Briefly, 3 ϫ 10 5 responder and irradiated (40 Gy) stimulator cells were placed in triplicate wells.…”
Section: Elispot Assaymentioning
confidence: 99%